2013
DOI: 10.2147/ijn.s45742
|View full text |Cite
|
Sign up to set email alerts
|

In situ fabrication of silver nanoparticle-filled hydrogen titanate nanotube layer on metallic titanium surface for bacteriostatic and biocompatible implantation

Abstract: Abstract:A silver nanoparticle (AgNP)-filled hydrogen titanate nanotube layer was synthesized in situ on a metallic titanium substrate. In the synthesis approach, a layer of sodium titanate nanotubes is first prepared on the titanium surface by using a hydrothermal method. Silver nitrate solution is absorbed into the nanotube channels by immersing a dried nanotube layer in silver nitrate solution. Finally, silver ions are reduced by glucose, leading to the in situ growth of AgNPs in the hydrogen titanate nanot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…[73][74][75]146] Others found reductions in bacterial counts in vitro up to 90% compared to commercially pure titanium on nano-Ti surfaces and up to 100% for nano-AgHA when tested against E. coli, S. epidermidis and S. aureus. [76][77][78][79][80][81][82] It has recently been shown that a titanium nanotube surface exhibited antimicrobial properties and down-regulated the glycosyltransferase genes of Strep. Mutans [83].…”
Section: Nanomaterialsmentioning
confidence: 99%
“…[73][74][75]146] Others found reductions in bacterial counts in vitro up to 90% compared to commercially pure titanium on nano-Ti surfaces and up to 100% for nano-AgHA when tested against E. coli, S. epidermidis and S. aureus. [76][77][78][79][80][81][82] It has recently been shown that a titanium nanotube surface exhibited antimicrobial properties and down-regulated the glycosyltransferase genes of Strep. Mutans [83].…”
Section: Nanomaterialsmentioning
confidence: 99%
“…And the study by AshaRani et al has demonstrated that silver nanoparticles disrupt cell membranes and induce apoptosis through oxidative damage (AshaRani et al, 2009). Moreover, it has been suggested that in orthopedic treatments, silver nanoparticles may detach from the grafts and cause damage to the surrounding cellular tissues (Wang et al, 2013). Pauksch et al have demonstrated that 10 μg/g of silver nanoparticles are toxic to BMSCs (Pauksch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%